2014
DOI: 10.1186/1479-5876-12-57
|View full text |Cite
|
Sign up to set email alerts
|

Bufalin attenuates the stage and metastatic potential of hepatocellular carcinoma in nude mice

Abstract: BackgroundAdvanced hepatocellular carcinoma (HCC) patients undergo significant tumor growth and metastasis. Here, we investigated bufalin for treating HCC, which exhibits anti-tumor activities in many tumor cell lines.MethodIn our experiment, HCCLM3-R cells were injected into nude mice to form subcutaneous human HCC tumors that were implanted into the liver to establish orthotopic transplantation tumor models. Bufalin was injected intraperitoneally at 1 or 1.5 mg/kg. LY294002 (100 mg/kg), a potent inhibitor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…Our previous study demonstrated that bufalin markedly inhibits proliferation and promotes apoptosis through endoplasmic reticulum stress in hepatocellular carcinoma cells (21). Experimental studies have shown that bufalin affects cancer cells by inhibiting the AKT pathway (22)(23)(24)(25). The present study demonstrated that intrinsic and acquired resistance to cisplatin can be diminished by bufalin, which affects the AKT pathway in GC cells.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our previous study demonstrated that bufalin markedly inhibits proliferation and promotes apoptosis through endoplasmic reticulum stress in hepatocellular carcinoma cells (21). Experimental studies have shown that bufalin affects cancer cells by inhibiting the AKT pathway (22)(23)(24)(25). The present study demonstrated that intrinsic and acquired resistance to cisplatin can be diminished by bufalin, which affects the AKT pathway in GC cells.…”
Section: Introductionsupporting
confidence: 60%
“…The present study demonstrated that activation of the AKT pathway contributes to intrinsic and acquired resistance to cisplatin, and blocking the AKT pathway with bufalin enhances the efficacy of cisplatin in GC cells. (20), has been tested in clinical trials to treat advanced hepatocellular carcinoma, non-small-cell lung cancer and pancreatic cancer (28); and has been shown experimentally to inhibit cancer through the AKT pathway (22)(23)(24)(25). In the present study, bufalin inhibited the activation of AKT and its downstream molecules GSK-3β, mTOR, S6K and 4EBP1; and when combined with cisplatin, inhibited proliferation and promoted apoptosis of GC cells by diminishing activation of the AKT y under normoxic and hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It is a component found in many Chinese traditional medicine. Bufalin has an antitumor effect against various malignancies such as hepatocellular and lung carcinoma (Zhang, 2014;Wu, 2014;Qiu et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Preceding findings have revealed that the anticancer activity of bufalin could be attributed to its prevention of cell proliferation, instruction of apoptosis, disturbance of the cell cycle, and modulation of the immune response 79. Earlier study of ours revealed that bufalin had convincing anticancer growth and reduced the metastatic potentials in the human hepatocellular carcinoma-transplanted tumor model, and the fundamental mechanism was in part mediated by the signaling pathway of the Akt–GSK3β–β-catenin–E-cadherin 10,11. These results indicated that bufalin might be a purposeful constituent for cancer treatment.…”
Section: Introductionmentioning
confidence: 77%